Finance, Informal Competition, and Expectations: A Firm-Level Analysis - Emanuele Brancati; Michele Di Maio; Aminur Rahman (Institute of Labor Economics (IZA), 2022)
This paper documents the link between finance and informal competition. Using longitudinal firm-level data, we show that formal firms that are more exposed to the competition of informal firms are less likely to apply for a bank loan. This result is not due to sample selection, omitted variable bias, or reverse causality, and it is robust to different econometric specifications, including the use of an IV strategy. As for the mechanism explaining our result, we show that firms more exposed to informal competition have worse expectations on future sales growth, which in turn are associated with a lower probability of loan application. Finally, we provide suggestive evidence excluding supply-side mechanisms that may explain heterogeneities in firms' access to finance.
Keywords: O16; E26; D84; D22; 330; finance; informality; competition; expectations; MENA countries